2009
DOI: 10.1002/app.30976
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl vinyl acetate copolymer—SrAl2O4:Eu,Dy and Sr4Al14O25:Eu,Dy phosphor‐based composites: Preparation and material properties

Abstract: New photoactive composite based on ethyl vinyl acetate (EVA) and SrAl 2 O 4 :Eu,Dy or Sr 4 Al 14 O 25 :Eu,Dy were prepared by melt mixing or extrusion methodologies. The phosphorescent behavior and material properties of the polymer-phosphor composites were studied. The morphology of the polymer and the composites were studied by using scanning electron microscopy (SEM), transmission electron microscopy (TEM), and energy dispersive X-ray spectroscopy (EDS). The SEM shows that the physical and chemical behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…These encapsulation procedures are complex, require elaborate equipment, and adversely affect the luminescence output. 53 (Fig. This procedure allowed the phosphor composites to be transparent, to exhibit good physical and chemical stability, and to be easily processed.…”
Section: Photoluminescent Phosphor Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…These encapsulation procedures are complex, require elaborate equipment, and adversely affect the luminescence output. 53 (Fig. This procedure allowed the phosphor composites to be transparent, to exhibit good physical and chemical stability, and to be easily processed.…”
Section: Photoluminescent Phosphor Compositesmentioning
confidence: 99%
“…The EVA matrix has been chosen because of its desirable properties such as UV stability, good clarity and gloss, resistance to crack, toughness, and heat‐sealing properties. The water intake and thermal and mechanical stability of the composites was studied, and the resulting luminescence spectra of the phosphor and the composites were compared . When compared the SrAl 2 O 4 :Eu,Dy and Sr 4 Al 14 O 25 :Eu,Dy phosphor, the highest intensity of luminescence emission was shown by the Sr 4 Al 14 O 25 :Eu,Dy phosphor (Figs.…”
Section: Photoluminescent Phosphor Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…17 The encapsulation (coating) of SrAl 2 O 4 :Eu 2+ ,Dy 3+ with an organic material, i.e., a polymer or polymer blend improves the dispersion state of the pigment in the organic paint because of chemical structure similarity. Mishra et al 18 coated the surface of SrAl 2 O 4 :Eu 2+ ,Dy 3+ with ethyl vinyl acetate (EVA). They found that the EVA-coated pigment particles achieved a uniform dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…2 Photoluminescent polymers are gaining interest in many applications, such as advertisement cards, playtoys, safety indicators, and luminous paints, due to the quality of emitted light and the ease of production. [3][4][5] Photoluminescent materials use photons as the energy source and can be separated into two subclasses: fluorescence and phosphorescence. Phosphorescence, focused in the present study, is a term of light emission of specific de-excitation process.…”
Section: Introductionmentioning
confidence: 99%